Gender comparisons of young adults' eating behavior regulation: Re-examination of the Regulation of Eating Behavior Scale (REBS). (1st July 2018) - Hamilton, Tessa; Hoffman, Jessica; Arsiwalla, Dilbur; Volpe, Robert; Schmidt, Ellyn; Gropper, Sareen
Abstract: The aim of this study was to evaluate the psychometric properties of the Regulation of Eating Behavior Scale (REBS) in mixed-gender, American samples and to evaluate how responses differed across male and female respondents. Responses were examined in a sample of 535 undergraduate students in the Southeastern United States. A confirmatory factor analysis was used to confirm the predicted factor structure; male and female participants were analyzed in a multi-group, unconstrained configural model, with male and female participants analyzed simultaneously to allow for multi-group comparisons within the same model. Additional analyses evaluated measurement invariance, reliability of the measure in the new sample, gender differences in subscale scores, and correlations across factors. Results of confirmatory factor analysis, multi-group by gender comparisons suggested that the factor structure did not vary across genders. In addition, factor structure was consistent with the findings of the original studies examining the psychometric property of the REBS, with the exception of the 'introjected regulation' subscale, which measures regulation of eating behaviors to avoid self-enforced consequences. Consistent with expectations, female participants' ratings were higher, on average, on more autonomous forms of eating regulation; however, contrary to expectations, scores did not differ significantly between males and females on more external forms of eating regulation. Conclusions, limitations, and implications are discussed.